DYSKUSJA WOKÓŁ PROJEKTÓW WYDAWNICZYCH W KORESPONDENCJI JERZEGO GIEDROYCIA I ALEKSANDRA WATA - Kudyba, Wojciech (Colloquia Litteraria, 2012)
A discussion on publishing projects in the correspondence between Jerzy Giedroyc and Aleksander Wat Having read a correspondence between Aleksander Wat and Jerzy Giedroyc from 1959–1967 (approximately 30 letters of each correspondent), the author notes that it concerns mainly professional issues, among others, Wat’s working in the post of the editor in Milan’s publishing house of Umberto Silva, who planned (the plans being carried out or not) to publish translations of books of Polish authors (among others, Noce i dnie by Maria Dąbrowska, Bolesław Chrobry by Gołubiew, Srebrne orły by Parnicki, Rodzinna Europa by Miłosz, Skrzydła ołtarza by Herling-Grudziński). An important topic – especially for Giedroyc – raised in these letters, is the picture of communism in the West, frequently wrongly interpreted there, and from the angle of this subject-matter Giedroyc organizes publishing plans in Literary Institute in Paris, among others he supports Wat in writing a book on a true facet of communist Russia – a collection Świat na haku i pod kluczem and Mój wiek [My Century], which were, however, to be published only after Wat’s death.